Hot corrosion behaviour of nanostructured zirconia in molten NaVO3 salt. Issue 13 (September 2017) - Wang, Jinshuang; Sun, Junbin; Zou, Binglin; Zhou, Xin; Dong, Shujuan; Li, Lifen; Jiang, Jianing; Deng, Longhui; Cao, Xueqiang
Abstract: Plasma sprayed coatings were fabricated from nanostructured yttria-stabilized zirconia powders (n-YSZ) with different crystalline grain sizes, prepared via sintering of nano ZrO2 -4 mol% Y2 O3 powders at different temperatures. The hot corrosion behaviour of both n-YSZ powders and their corresponding coatings with sodium metavanadate (NaVO3 ) were investigated at 700 °C. During hot corrosion, NaVO3 reacts with Y2 O3 in YSZ to form YVO4, leading to a tetragonal to monoclinic destructive phase transformation of YSZ. The crystalline grain size of n-YSZ powders did not affect the hot corrosion mechanisms of both the n-YSZ powders and their corresponding coatings. However, compared with n-YSZ powders, the coatings were more easily corroded, and the coatings formed from starting powders with crystalline grain sizes <30 nm featured better degradation resistance to hot corrosion.